Poplar tree for innovative plantation models - Bergante, Sara (Annals of Silvicultural Research, 2024)
The traditional poplar cultivation does not represent the only way to produce poplar wood: new market opportunities and new more sustainable cultivation models are appearing on the international scene. We are only reconsidering past solutions in a modern key and with new knowledges and technologies able to improve the productions through more sustainable, resilient, cultivation models for the adaptation to climate and market changes. In this note three alternative models (to traditional poplar growth) suitable for production of plywood, packaging, panels, pulp for paper, biomass and for environment services, are described and discussed: high-density model (HD), polycyclic plantation model (PP) and agroforestry (AF).